Rasionalisme Dan Kritik Dalam Dunia Filsafat - Pristiwiyanto, Pristiwiyanto; Mahfud, Muhammad (RISDA : Jurnal Pemikiran dan Pendidikan Islam, 2021)
In its development in the world of philosophy, several isms / philosophical understandings have emerged that cannot be avoided. Rationalism is one of the philosophies that teaches that reason is the main source of science. Characters who use reason / ratio as the main source of knowledge have been practiced since the ancient Greek era of Thales to modern philosophy such as Rene Descartes, Baruch Spinozoa, G.W. Leibniz, and Nicolas Malbebranche. This criticism of rationalism shows that not all concepts of rationalism can be applied to practical everyday life, besides that reason / ratio is not the only main source of a science.